SAE Technical Paper Series 2017
DOI: 10.4271/2017-01-1031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Intake Plenum Design on the Scavenging Process in a 2-Stroke Boosted Uniflow Scavenged Direct Injection Gasoline (BUSDIG) Engine

Abstract: In this study, the effect of the intake plenum design on the scavenging process in a newly proposed 2-stroke Boosted Uniflow Scavenged Direct Injection Gasoline (BUSDIG) engine was studied in detail by three dimensional (3D) computational fluid dynamics (CFD) simulations. In the BUSDIG engine, the intake scavenge ports are integrated into the cylinder liner and their opening and closure are controlled by the movement of piston top while exhaust valves are placed in the cylinder head. In order to accommodate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The centrally mounted DI injector and spark plug on the cylinder head were positioned to place the spray recirculation region around the spark plug. The key engine design parameters, including engine bore/stroke ratio, 39 scavenge port angles, 4042 opening profiles of scavenge ports and exhaust valves 43 and intake plenum, 44 have been analysed and evaluated for optimal scavenging performance and in-cylinder flow motions. A full review of the BUSDIG engine concept can be found in a recently published article.…”
Section: Specifications Of the Two-stroke Busdig Enginementioning
confidence: 99%
“…The centrally mounted DI injector and spark plug on the cylinder head were positioned to place the spray recirculation region around the spark plug. The key engine design parameters, including engine bore/stroke ratio, 39 scavenge port angles, 4042 opening profiles of scavenge ports and exhaust valves 43 and intake plenum, 44 have been analysed and evaluated for optimal scavenging performance and in-cylinder flow motions. A full review of the BUSDIG engine concept can be found in a recently published article.…”
Section: Specifications Of the Two-stroke Busdig Enginementioning
confidence: 99%
“…Some of these mechanisms afford the potential to realize variable timing of the exhaust versus the intake, with the ability to control combustion through homogeneous charge compression ignition-type combustion systems, e.g. the portpoppet engine which in production form has already used electrohydraulic continuously-variable exhaust valve control [10,16] and for which exhaust cam profile switching has been proposed for automotive use [17]. Also, partly because of the improved bore distortion performance mentioned above, all of those engines used as examples employed or employ a wet sump lubrication system, which in theory could permit oil consumption levels approaching those of 4-strokes [2], and, through their proven applications in ships, the durability to eclipse automotive engines.…”
Section: -Stroke Scavenging Systems Studiedmentioning
confidence: 99%
“…In light of the advantages of the 2-stroke operation, a novel 2-stroke Boosted Uniflow Scavenged Direct Injection Gasoline (BUSDIG) engine has been designed and extensively researched at Brunel since 2015 [7]. Key designs of the proposed BUSDIG engine, including engine bore/stroke ratio [8], scavenge ports [9][10][11], opening profiles of scavenge ports and exhaust valves [12], intake plenum [13], injection strategies [14,15] and piston shape [16] have been systematically studied to optimise the scavenging performance and charge preparation of the BUSDIG engine.…”
Section: Introductionmentioning
confidence: 99%